Exploring Stakeholder Collaboration in Addressing Watershed Degradation - Muchtar, Asikin (LPPPIPublishing, 2025)
The degradation of the Tallo watershed has become an urgent environmental issue in South Sulawesi, especially due to urbanization pressures, domestic waste pollution, and declining quality of aquatic ecosystems. This research aims to explore the collaboration of stakeholders in addressing watershed degradation by emphasizing the role, interaction, and synergy between local governments, local communities, civil society organizations, and academia. The research uses a descriptive qualitative approach with a case study design on the Tallo watershed. The data was obtained through in-depth interviews with eight key informants consisting of government representatives, community leaders, environmental activists, and academic experts, and was complemented by field observations and analysis of policy documents. Data analysis was carried out using thematic analysis techniques and stakeholder mapping to identify patterns of collaboration and institutional dynamics. The results show that collaboration efforts are still partial, dominated by government programs, while the participation of the community and the private sector is relatively limited. However, effective multi-stakeholder coordination practices are found in river boundary rehabilitation activities and community-based pollution control initiatives. This study concludes that strengthening collaborative governance, community capacity building, and integration of cross-sectoral roles are important strategies in sustainable watershed management. Theoretically, this study enriches the study of environmental governance and multi-stakeholder collaboration, while practically providing policy recommendations to improve the effectiveness of the management of the Tallo watershed in an inclusive and participatory manner.